Factors Influencing the HRD Climate of an Organization - Kumari, Neeraj (International Journal of Management and Sustainability, 2013)
The aim of the study was to find out which factor (s) influence the HRD climate of the company. The descriptive research design was under taken with the help of the structured questionnaire to study the OCTAPACE culture of Spanco Ltd. which was based on the responses of the various levels of employees working in it. Thesample consistsof 59 employees. Employees believe that the top management gives importance to the human resource and all the employees are treated humanely in the organization. The climate is also favourable in terms of employee being handled with care by seniors as they understand the mistake and do not take any strict disciplinary action such as punishing or discouraging.There is also a fair share of management involvement in making work enjoyable. Good part of Spanco regarding HRD is that top management understands the importance of human resource and actually translates that realization into day to day practice and HR policies.In conclusion, the overall HRD climate of Spanco is encouraging. There is a keen interest of top management in HRD and there is a high team spirit and employees take training seriously. Organizational belonging of employees is also high. Despite of such positive base for HRD, HRD mechanism needs improvisation in a systematic way.